Peningkatan Hasil Belajar Siswa Pada Pembelajaran IPA Menggunakan Strategi Generatif Di Sekolah Dasar - Indriani Sevti Annisa (Jurnal Family Education, 2021)
This research was conducted due to the four grade student`s low learning achievement at SDN 17 Manggis Ganting Kota Bukittinggi. The aim of this research was to describe the improvement of the student`s learning achievement in Natural Science by using generatif strategy in the four grade of SDN 17 Manggis Ganting Kota Bukittinggi. This was a classroom action research which applied qualitative and quantitative approaches. The result of the research indicated that the student`s learning achievement improved from 74 in the first cycle into 81,65 in the second cycle. Hence, the use of generatif strategy could improve the student’s learning achievement in Natural Science in the four grade of SDN 17 Manggis Ganting Kota Bukittinggi.